Code Switching Found In Selected Video On Najwa Shihab Youtube Channels - Pradnyadita, Ni Putu Krisna Putri; Sulatra, I Komang; Marantika, I Made Yogi (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
This study concerns with the code switching found in Najwa Shihab YouTube channel. The aims of this study are; (1) to find out the types of code switching found in selected video on Najwa Shihab YouTube channels; and (2) to analyze the reason of code switching found in Najwa Shihab selected videos. Descriptive qualitative method was used for analyzing the data from three selected videos. The theory was applied are from Poplack (as cited in Romaine, 1989) to classify the types of code switching and theory proposed by Hoffman (1991) to identify and analyze the reasons of code switching. The results presented three types of code switching and seven reason for code switching were found. Intra-sentential switching is the most dominant types of code switching found in those three selected videos and the most dominant reason found in the three selected videos is talking about a particular topic.